PENGARUH LAMA PENYIMPANAN DAGING AYAM PADA SUHU RUANG DAN REFRIGERATOR TERHADAP ANGKA LEMPENG TOTAL BAKTERI DAN ADANYA BAKTERI Salmonella sp - Syahmi Edi; Roro Shofiyah Nur Rahmah (JBIO: jurnal biosains (the journal of biosciences), 2018)
The purpose of this research is to understand the existence of bacteria contamination as an indicator of consumption feasibility in chicken meat. The research used 100 grams of chicken meat sample from on of the traditional market in Medan. Each sample was grown on Nutrient Agar and Salmonella Shigella Agar media. If the colony grows on SSA media that appear convex and clear yellow, it will followed by biochemical tests including Triple Sugar Iron Agar and Simmons Citrate Agar. The results showed that chicken meat storage at room temperature for 9 hours and 12 hours above maximum value of SNI (above 1 x 106), that is 173 x 104 and 354 x 104. The results of analysis of variance samples of chicken meat stored at room temperature showed the value of Fcount (101,356) > Ftable (2,866), storage duration of chicken meat at the room temperature have a significant effect to the total plate bacteria count. The results of analysis of variance samples of chicken meat stored at refrigerator temperature showed the value of Fcount (21,443) > Ftable (2,866), storage duration of chicken meat at the refrigerator temperature have a significant effect to the total plate bacteria count. Based on the results of further tests using BNT test obtained that the storage duration of chicken meat at room temperature for 3 hours have a very significant effect on the total plate bacteria count. The results of further tests using BNT test, that chicken meat storage at room temperature have a very significant effect between treatment for 0 hours and 3 hours of storage to total plate bacteria count. While at refrigerator temperature have a very significant effect between treatment for 9 hours and 12 hours of storage to total bacterial plate number. The results showed that 2 samples from 10 samples tested were positive contaminated by Salmonella sp. This indicates that the quality of chicken meat that has been stored for more than 9 hours at room temperature does not accord suit to the standards based on Indonesian Nasional Standard. Keywords: Chicken Meat, Storage Duration, Total Plate Bacteria Count, Salmonella sp.